2008
DOI: 10.1111/j.1365-2702.2008.02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Italian nurses’ perception of the avoidability of problems affecting older people with multiple chronic diseases

Abstract: To reflect on unavoidable nursing problems and related factors is important for the potential consequences of clinical judgment on patients and on nursing care and for ethical implications. The factors affecting avoidable or unavoidable problems need strategic and individualised action to develop healthcare plans including the older people themselves, their families, and members of a multidisciplinary team and to provide adequate resources and educational programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
(29 reference statements)
0
10
0
1
Order By: Relevance
“…The 11 included studies (Table 3) were undertaken in Australia (Byrne et al, 2020; McNamara et al, 2017; Peart et al, 2019), the United Kingdom (O’Conner et al, 2018; O’Brien et al, 2011), Sweden (Grundberg et al, 2016; Karlsson & Karlsson, 2019), Canada (Heale et al, 2018; MacDonald et al, 2018), Italy (Saini et al, 2008) and New Zealand (Stokes et al, 2017). Nine papers were published in the period 2016–2019; two papers were published 2008–2011.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 11 included studies (Table 3) were undertaken in Australia (Byrne et al, 2020; McNamara et al, 2017; Peart et al, 2019), the United Kingdom (O’Conner et al, 2018; O’Brien et al, 2011), Sweden (Grundberg et al, 2016; Karlsson & Karlsson, 2019), Canada (Heale et al, 2018; MacDonald et al, 2018), Italy (Saini et al, 2008) and New Zealand (Stokes et al, 2017). Nine papers were published in the period 2016–2019; two papers were published 2008–2011.…”
Section: Resultsmentioning
confidence: 99%
“…Methods used to analyse the qualitative data of the included studies included thematic analysis (Byrne et al, 2020; O’Brien et al, 2011; O’Conner et al, 2018; Stokes et al, 2017); content analysis (Grundberg et al, 2016; Karlsson & Karlsson, 2019; Saini et al, 2008); interpretive analysis (Heale et al, 2018); narrative analysis (MacDonald et al, 2018); constant comparison (McNamara et al, 2017) and interpretive phenomenological analysis (Peart et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Los estudios reportan como lo enfermeros en el domicilio buscan mejorar los procesos organizativos, la participación de los miembros de la familia y sus propias habilidades y sentido de propósito 23,24 . Presentando comportamientos de enfermería relacionados con las necesidades físicas y necesidades psicosociales del paciente.…”
Section: Discussionunclassified
“…The marginalisation and exclusion of patient perspective in risk prevention discourses are argued to lead to a tolerance of lower standards or expectations for particular groups, such as older people at risk of pressure injury, people with learning disabilities (Tregelles, ) and those experiencing debilitating side effects from psychiatric medications (Wand, ). Foregrounding the notion of unavoidable risk of harm in nursing practice, Saiani, Viviani, Chissale, and Palese () reported that nurses perceived factors such as multiple disease interactions, refusal of care and limited monitoring of care provided in the community for older people with multiple long‐term health problems as unavoidable.…”
Section: A Critical Lens On the Concept Of Unavoidable Harmmentioning
confidence: 99%